PEMBUATAN DAN KARAKTERISASI MEMBRAN ELEKTRODA SELEKTIF ION Cu(II) MENGGUNAKAN IONOFOR Na2S SEBAGAI SENSOR KIMIA - Rosyada, Amrina; Arif, Moh. Syaiful; Panggabean, Aman Sentosa (JURNAL ATOMIK, 2025)
Preparation and characterization of Cu(II) ion selective electrode membranes based on polyvinyl chloride (PVC) using sodium sulfide (Na 2 S) as the ionophore has been done. The use of PVC polymer functions as a material that strengthens the properties of the membrane mixed with Na 2 S to form a homogeneous membrane and can reduce the risk of leaks in the membrane used. However, PVC has stiff properties, so a plasticizer in the form of DOP was needed to reduce intermolecular forces and make the membrane elastic. The preparation was carried out with the composition Na 2 S : PVC : DOP, namely 6 : 3 : 1. The membrane was doped with CuSO 4 solution for 7 days and the Cu 2+ ESI performance was measured to increase the optimal conductivity of the membrane, it is done by doping the membrane, namely by inserting 1 M Cu 2+ dopant metal. The ESI Cu 2+ performance results show a solution composition of 1:2 CuSO 4 :KNO 3 and works well in the composition range 10 -5 - 10 -1 M, with a Nernst factor value of 28.9 mV/decade and a detection limit of 1.01×10 -5 M. The response time of ESI Cu 2+ was 10-60 seconds and can be used for 3 days. ESI Cu 2+ works in the pH range 4-6 and the presence of interfering ions Cd 2+ , Zn 2+ , Cl-, NO 3 - and SO 4 2- does not affect the performance of ESI Cu 2+.